Reaction of Coniferous Forest Vegetation to Particulate Deposition Under Alkaline Pressure - Świercz, Anna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
The aim of this study was to determine direction, rate and character of the changes in coniferous forest communities caused by anthropogenic stress factors (alkaline emission and imission) changing with time. To fulfil this goal, we have performed comprehensive studies of soils and plants at the study sites located in coniferous forest communities remaining under direct influence of cement and lime industry in the Świętokrzyskie Voivodeship. There were differences in the accumulation of elements in pine needles collected at alkalized sites in comparison with needles from the control site: Ca content was 2.5 times higher and Cu, Pb and Sr contents were 2–3 times higher, while Al and Fe, and Mn contents were twice and 10 times lower respectively. SEM analysis of morphological features of pine needle surface, in particular degree of preservation of epicuticular waxes can be as an indicator of assimilatory organ degeneration caused by dust deposition which induces wax layer erosion. Declining species number and biodiversity, particularly conspicuous at the Sitkówka site, was a general tendency observed over the study period (from 18 to 10 years). Other noticeable processes include slow regenerative changes of the community with a tendency towards higher contribution of acidophilic coniferous forest species with lower light and temperature requirements and suppression of meadow, ruderal and associated taxa. Further studies are required in order to define succession rate and direction of changes in species composition of these communities.